Characteristics of adverse drug reactions and risk management strategies for methylprednisolone sodium succinate in the treatment of idiopathic sudden sensorineural hearing loss: a clinical study of 1026 patients - Wu, Ting; Tang, Yu; Yan, Sinan; Meng, Jie; He, Shuangba; Meng, Wei (Frontiers in Medicine, 2025)
ObjectiveTo systematically analyze the patterns, risk factors, and clinical management strategies of adverse drug reactions (ADRs) associated with methylprednisolone sodium succinate in the treatment of idiopathic sudden sensorineural hearing loss (ISSNHL).MethodsA retrospective study was conducted on 1026 ISSNHL patients treated with methylprednisolone sodium succinate at Nanjing Tongren Hospital from January 2020 to December 2024. The incidence, types, severity, and outcomes of ADRs were recorded. Multivariate logistic regression was used to identify risk factors, and evidence-based intervention recommendations were proposed.ResultsThe overall ADRs incidence was 17.2% (177/1026), with gastrointestinal reactions (43.5%), elevated blood glucose (29.9%), and neuropsychiatric symptoms (18.1%) being the most common. Advanced age (≥60 years, OR = 2.24) and diabetes (OR = 3.15) were independent risk factors for ADRs (both P < 0.05). Symptoms were alleviated in 98.3% of patients after intervention, and treatment was discontinued in 3 cases due to severe hyperglycemia.ConclusionThe risk of ADRs from methylprednisolone sodium succinate is closely related to patients’ underlying conditions and treatment regimens. A stratified warning system and optimized individualized treatment strategies are necessary.